RELATIONSHIP OF ABSOLUTE AND RELATIVE LOWER EXTREMITIES STRENGTH AND THE EFFICIENCY OF VAULT PERFORMANCE IN GYMNASTICS - Adis Tabaković; Muhamed Tabaković; Almir Atiković; Semir Mašić; Amila Hodžić (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
The aim of this research was to examine the relationship between absolute and relative lower extremity strength and the efficiency of gymnastics vault performance. Thirty healthy, physically active male students (age: 20.84 ± 0.99 years; height: 179.46 ± 5.91 cm; body weight: 73.88 ± 6.43 kg) from the Faculty of Sports and Physical Education participated in the study. Absolute lower extremity strength was assessed by measuring the maximum load lifted (in kg) during a back squat (1RM). Relative lower extremity strength was calculated by dividing the estimated 1RM back squat by the participant's body weight (1RM/BW). Two types of vaults-the squat through (ST) and the front handspring (FHS)-were used to evaluate vault performance efficiency. Three criterion variables were applied: (d1) distance from the springboard in front of the vault, (d2) distance of landing beyond the vault, (d1 - d2) the difference between d1 and d2, and (pt) overall vault performance rating. The results showed statistically significant and strong correlations between both absolute and relative lower extremity strength and the variables measuring vault performance efficiency. The strongest correlations were observed for (d1), followed by (d2), (pt), and (d1 - d2). These findings can serve as guidelines for developing both absolute and relative lower extremity strength, which may lead to improved performance in gymnastics vaults.